2019
DOI: 10.3390/atmos10110708
|View full text |Cite
|
Sign up to set email alerts
|

Variations in Greenhouse Gas Fluxes in Response to Short-Term Changes in Weather Variables at Three Elevation Ranges, Wakiso District, Uganda

Abstract: Weather conditions are among the major factors leading to the increasing greenhouse gas (GHG) fluxes from the agricultural soils. In this study, variations in the soil GHG fluxes with precipitation and soil temperatures at different elevation ranges in banana–coffee farms, in the Wakiso District, Uganda, were evaluated. The soil GHG fluxes were collected weekly, using the chamber method, and analyzed by using gas chromatography. Parallel soil temperature samples were collected by using a REOTEMP soil thermomet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 85 publications
0
12
0
Order By: Relevance
“…Soil temperature significantly influences soil N 2 O fluxes by increasing microbial activities responsible for N 2 O emissions in soil [27]. Nitrous oxide emissions increase with an increase in soil temperature due to advanced decomposition rates of organic matter [58]. An increase in N 2 O emissions with rising temperature can be associated with increased nitrogen mineralization, hence higher availability of nitrogen lost as N 2 O fluxes [27].…”
Section: Effects Of Soil Temperature and Elevation On N 2 O Emissions In Ssamentioning
confidence: 99%
See 3 more Smart Citations
“…Soil temperature significantly influences soil N 2 O fluxes by increasing microbial activities responsible for N 2 O emissions in soil [27]. Nitrous oxide emissions increase with an increase in soil temperature due to advanced decomposition rates of organic matter [58]. An increase in N 2 O emissions with rising temperature can be associated with increased nitrogen mineralization, hence higher availability of nitrogen lost as N 2 O fluxes [27].…”
Section: Effects Of Soil Temperature and Elevation On N 2 O Emissions In Ssamentioning
confidence: 99%
“…Atmospheric temperature also influences N 2 O emissions. For instance, Fatumah et al [58] reported higher N 2 O emissions in higher altitudes (1200-1300 m above sea level (asl)) characterized with low temperatures as compared to low altitudes (1100 to 1200 m and 900 to 1100 m asl) with higher temperature in Uganda. Further, in Kenya, higher soil N 2 O emissions were observed in Kaptumo with an elevation of 2000 m asl than Kolero with an elevation of 1250 m asl [42].…”
Section: Effects Of Soil Temperature and Elevation On N 2 O Emissions In Ssamentioning
confidence: 99%
See 2 more Smart Citations
“…GHGe from agricultural soil are strongly correlated with temperature and precipitation [17,18]. Soil microorganisms play a critical role in driving biochemical processes that lead to GHGe and are sensitive to temperature changes [19,20].…”
Section: Introductionmentioning
confidence: 99%